ANALISIS FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA INDUSTRI OTOMOTIF DAN KOMPONENNYA DI BURSA EFEK INDONESIA - Darmono, Darmono (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2018)
The aim of the study was to determine structure of assets, sales growth, operating leverage, profitability and, tax growth affect the capital structure and to determine the most dominant factors affect the capital structure of the automotive industry and components in the Indonesia Stock Exchange. The analysis in this research use multiple linear regression. The results showed that simultaneously (asset structure, sales growth, operating leverage, profitability, and tax growth) did not affect the capital structure. The result of t test shows that Growth Tax has the highest partial determinant coefficient value in automotive industry and its component in Indonesia Stock Exchange.